The Role Of Youtube Live Streaming In The Agunza Boyolali Folk Performing Arts Group - Tulus Pambudi; Denis Setiaji (Sean Institute, 2025)
This article aims to describe the role of YouTube live streaming in the Agunza folk performing arts group in Boyolali. It was a qualitative research with ethnographic design. That research was conducted from October 2024 to January 2024 in Gunungsari, Senden Village, Selo District, Boyolali with three main speakers from the members of Agunza group and YouTube content creator. Data were collected using observation, interview, and documentation techniques. Data analysis was carried out by applying an interactive analysis model adopted from Miles, et al (2014), namely data reduction, data display, and verification. The result shows that the role of YouTube live streaming is vital for the Agunza group, which is one of the strategies applied to promote regional arts, form trends to watch and watch, and create inter-connectivity space for folk performing arts.